The moderating role of psychological capital in the relationship between workplace bullying and job burnout among nurses in Saudi Arabia: A cross-sectional study - Abou Zeid, Mennat Allah G.; Ibrahim, Ibrahim Abdullatif (Belitung Nursing Journal, 2026)
Background: Workplace bullying remains a pervasive problem in nursing, adversely affecting nurses’ well-being and professional functioning. Prolonged exposure to bullying is associated with emotional exhaustion and job burnout. However, the potential buffering role of internal psychological resources, particularly psychological capital, has not been sufficiently examined. Objective: This study aimed to explore the association between workplace bullying and job burnout among hospital nurses and examined whether psychological capital moderates this relationship. Methods: A cross-sectional study was conducted with 209 nurses from two hospitals between July and September 2025. Data were collected using the Short Negative Acts Questionnaire, the Work-Related Burnout subscale of the Copenhagen Burnout Inventory, the Psychological Capital Questionnaire, and a demographic and professional characteristics form. Data analysis included descriptive statistics, independent t-tests, one-way ANOVA, Pearson’s correlation coefficients, and moderation analysis using PROCESS macro (Model 1). Results: Nurses reported moderate levels of workplace bullying (M = 2.31, SD = 1.12) and job burnout (M = 2.44, SD = 0.91). Psychological capital was relatively high (M = 4.89, SD = 1.08), including optimism (M = 4.93, SD = 1.09), hope (M = 4.96, SD = 1.13), self-efficacy (M = 4.77, SD = 1.19), and resilience (M = 4.89, SD = 1.17). Job burnout differed significantly across age groups (p = 0.043). Workplace bullying and job burnout varied by educational level (p = 0.019 and p = 0.021, respectively), and workplace bullying differed by gender (p = 0.001). Moderation analysis indicated that workplace bullying was positively associated with job burnout (B = 0.472, p < 0.001), whereas psychological capital was negatively associated with burnout (B = -0.135, p < 0.01). The interaction between workplace bullying and psychological capital was significant (B = 00.106, p < 0.01), indicating that psychological capital attenuated the positive association between workplace bullying and job burnout. Conclusion: Psychological capital functions as a protective factor that buffers the adverse impact of workplace bullying on nurses’ job burnout. These findings highlight the importance of strengthening nurses’ psychological resources through organizational strategies and resilience-enhancing interventions to promote well-being and reduce burnout risk.